2000
DOI: 10.1136/oem.57.11.745
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure tocis-1,3-dichloropropene: biological effect monitoring of kidney and liver function

Abstract: Objectives-To investigate the possible eVects of occupational exposure to the nematocide cis-1,3-dichloropropene (cis-DCP) on function of the kidney and liver in the starch potato growing region in The Netherlands. Methods-The study involved 13 commercial application workers exposed to cis-DCP for 117 days, and 22 matched control workers. The inhalatory exposure of the application workers was estimated from biological monitoring data. All workers collected urine and serum samples before, during, and after the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Irritant cutaneous effects due to contact with 1,3‐dichloropropene are well known and reported in its technical data sheet. In a review, Verplanke et al (3) showed that occupational exposure to 1,3‐dichloropropene was not associated with adverse effects on the kidney or liver. To our knowledge, no previous cases of sensitization to this nematocide have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Irritant cutaneous effects due to contact with 1,3‐dichloropropene are well known and reported in its technical data sheet. In a review, Verplanke et al (3) showed that occupational exposure to 1,3‐dichloropropene was not associated with adverse effects on the kidney or liver. To our knowledge, no previous cases of sensitization to this nematocide have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…A subsequent comprehensive study in Dutch potato field fumigation workers conducted over the whole of the fumigation season failed to observe treatment-related toxicity (Verplanke et al, 2000). Workers were exposed to a range of 0.1-9.5 mg/m 3 cis-1,3-dichlororporpene and a number of parameters were measured before, during, and following the fumigation season.…”
Section: Use Experiencementioning
confidence: 99%